Analysis of the Performance for Bystanders’ Cardiopulmonary Resuscitation in Geriatric and Out-of-Hospital Cardiac Arrested Patients - Junwon Bae; Jaehoon Oh; Sanghyun Lee; Tae Ho Lim; Hyunggoo Kang; Juncheol Lee (Annals of Geriatric Medicine and Research, 2016)
Background: The purpose of this study was to determine if there were changes in bystanders’ chest compression performance and activation of emergency medical services in geriatric and out-of-hospital cardiac patients following the institution of the 2010 International Resuscitation Guidelines and 2008 Good Samaritan Law in South Korea. Methods: This is a retrospective observational study using medical records, and including patient charts and an Utstein Style database in a tertiary hospital. We analyzed the existence of chest compression performance by bystanders, the required time from recognition of cardiac arrest to activation of 119 for emergency medicine services, and the required time from activation of 119 to arrival on the scene from 2005-2014. The data were compared after dividing the years into 2 groups: 2005–2009 and 2010–2014. Results:Of 317 geriatric and out-of-hospital cardiac arrest patients, 261 were eligible for this study. Twelve cases were excluded, and a total of 249 were analyzed. Bystander-initiated chest compression was higher from 2010-2014 than from 2005–2009 (32 [20.13%] and 7 [7.78%], p=0.031, respectively). However, the time required from recognition of cardiac arrest to 119 activation and from 119 activation to arrival was not significantly different between the 2 groups (all p＞0.05). Conclusion: It is possible that the release of the 2010 International Resuscitation Guidelines and the 2008 Good Samaritan Law may have influenced the potential incremental increase in chest compression performance by a bystander in geriatric and out-of-hospital cardiac arrest patients.